131k views
0 votes
Solve for v -7 v+3 = -63

2 Answers

5 votes

Answer:

Explanation:

-7v+3=-63

-7v=-63-3

-7v=-66

-7v-7=-66÷-7

V=9.4

User Purkhalo Alex
by
5.4k points
0 votes

Answer:

v = 66/7

Explanation:

Step 1: Write equation

-7v + 3 = -63

Step 2: Solve for v

Subtract 3 on both sides: -7v = -66

Divide both sides by -7: v = 66/7

Step 3: Check

Plug in x to verify if it's a solution.

-7(66/7) + 3 = -63

-66 + 3 = -63

-63 = -63

User Pradeep Singh
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.